A chemically stable PVD multilayer encapsulation for lithium microbatteries. (4th September 2015) - Ribeiro, J F; Sousa, R; Cunha, D J; Vieira, E M F; Silva, M M; Dupont, L; Goncalves, L M
Abstract: A multilayer physical vapour deposition (PVD) thin-film encapsulation method for lithium microbatteries is presented. Lithium microbatteries with a lithium cobalt oxide (LiCoO2 ) cathode, a lithium phosphorous oxynitride (LiPON) electrolyte and a metallic lithium anode are under development, using PVD deposition techniques. Metallic lithium film is still the most common anode on this battery technology; however, it presents a huge challenge in terms of material encapsulation (lithium reacts with almost any materials deposited on top and almost instantly begins oxidizing in contact with atmosphere). To prove the encapsulation concept and perform all the experiments, lithium films were deposited by thermal evaporation technique on top of a glass substrate, with previously patterned Al/Ti contacts. Three distinct materials, in a multilayer combination, were tested to prevent lithium from reacting with protection materials and atmosphere. These multilayer films were deposited by RF sputtering and were composed of lithium phosphorous oxide (LiPO), LiPON and silicon nitride (Si3 N4 ). To complete the long-term encapsulation after breaking the vacuum, an epoxy was applied on top of the PVD multilayer. In order to evaluate oxidation state of lithium films, the lithium resistance was measured in a four probe setup (cancelling wires/contact resistances) and resistivity calculated, considering physical dimensions. A lithium resistivity of 0.16 Ω μ m was maintained for more than a week. This PVD multilayer exonerates the use of chemical vapour deposition (CVD), glove-box chambers and sample manipulation between them, significantly reducing the fabrication cost, since battery and its encapsulation are fabricated in the same PVD chamber.